Nepotisme dalam Perspektif Hadis Maudhu’i - Wijaya, Abdi (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2012)
Nepotism is an attitude that can be detrimental to society. it could have entered into a variety of bureaucratic system. Its existence has become a debate in a variety of scientific perspective. In the Islam perspective, particularly Hadith, it was found that nepotism has number of Hadiths, among the allowing and banning. Based on various Hadith, it can be stated that the nepotism between banning and allowing depends on condition.